Well, honey, if m equals 6, then 5 times m is just 5 times 6, which equals 30. It's as simple as that, no need to overcomplicate things. Just plug in that value of m and you've got your answer faster than you can say "math is fun."
5m-7m = 12 -2m = 12 -2m/-2 = 12/-2 m = -6
m = -1
m = 4
5m - 5 + 2 = 1 Therefore, 5m - 3 = 1 5m = 4 m = 4/5 m = 0.8
-5m-3+4 = 11 -5m = 11+3-4 -5m = 10 m = -2
5m-7m = 12 -2m = 12 -2m/-2 = 12/-2 m = -6
5m=40/5=/5m=8
To solve the equation 5m + 3 = 3m + 9, you need to isolate the variable m. Start by subtracting 3m from both sides to get 2m + 3 = 9. Then, subtract 3 from both sides to get 2m = 6. Finally, divide by 2 to find m = 3.
m = -1
2 - 7n = 6therefore 7n = 2 - 6 = -4 and so n = -4/7 Then 5m + 7n = 6.4 becomes 5m - 4 = 6.4 so that 5m = 10.4 and then m = 10.4/5 = 2.08
m = 4
m = 4
5m - 6 + m + 10 = 6m + 4
40
5m - 5 + 2 = 1 Therefore, 5m - 3 = 1 5m = 4 m = 4/5 m = 0.8
Assuming -5m=11:Divide both sides by -5: m= -11/5And you have what m equals.
-3m = 5m+8 -3m-5m = 8 -8m = 8 m = -1